Highly Amino Acid Selective Hydrolysis of Myoglobin at Aspartate Residues as Promoted by Zirconium(IV)‐Substituted Polyoxometalates1. (7th May 2015) - Ly, Hong Giang T.; Absillis, Gregory; Janssens, Rik; Proost, Paul; Parac‐Vogt, Tatjana N.
Abstract SDS‐PAGE/Edman degradation and HPLC MS/MS showed that zirconium(IV)‐substituted Lindqvist‐, Keggin‐, and Wells–Dawson‐type polyoxometalates (POMs) selectively hydrolyze the protein myoglobin at AspX peptide bonds under mildly acidic and neutral conditions. This transformation is the first example of highly sequence selective protein hydrolysis by POMs, a novel class of protein‐hydrolyzing agents. The selectivity is directed by Asp residues located on the surface of the protein and is further assisted by electrostatic interactions between the negatively charged POMs and positively charged surface patches in the vicinity of the cleavage site.